Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.5194/npg-19-215-2012
|View full text |Cite
|
Sign up to set email alerts
|

Topological complexity of frictional interfaces: friction networks

Abstract: Abstract. Through research conducted in this study, a network approach to the correlation patterns of void spaces in rough fractures (crack type II) was developed. We characterized friction networks with several networks characteristics. The correlation among network properties with the fracture permeability is the result of friction networks. The revealed hubs in the complex aperture networks confirmed the importance of highly correlated groups to conduct the highlighted features of the dynamical aperture fie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…The method was used over the recorded time-series from acoustic transducers. A similar method has been used on real-time contact areas and apertures of frictional interfaces2930. Other techniques-also-have been introduced into the study of time series analysis, such as the approaches based on the concept of a quasi-periodic cycle43 correlations44 visibility45 transition probabilities46 recurrence analysis (phase-space reconstruction)474849.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The method was used over the recorded time-series from acoustic transducers. A similar method has been used on real-time contact areas and apertures of frictional interfaces2930. Other techniques-also-have been introduced into the study of time series analysis, such as the approaches based on the concept of a quasi-periodic cycle43 correlations44 visibility45 transition probabilities46 recurrence analysis (phase-space reconstruction)474849.…”
Section: Methodsmentioning
confidence: 99%
“…We use a “closeness” metric: . To choose a threshold level, we follow the employed method in2930, in which the minimum variation of local flow energy with the threshold level is considered as a criterion to the best threshold level. To precisely analyze a time series with the aforementioned methods and reduce possible errors due to the limited number of stations, we set m = 1 (equal to each recorded point).…”
Section: Methodsmentioning
confidence: 99%
“…In Fig. 1d of Ghaffari and Young (2012b), we showed that selecting the threshold level by using the minimum variation of B.C versus ξ is equivalent with finding the most stable structures in networks. We note that the truncation level (or an interval of that) determines the characteristics of the network.…”
Section: Network Constructionmentioning
confidence: 99%
“…Weathering impacts the transport properties and permeability of the rock (Brown, 1989;Brown et al, 1998;Regenauer-Lieb et al, 2013b, 2013aTsang & Witherspoon, 1981, 1983, and the diffusion and transport of solutes into the rock (Bear et al, 1993;Grisak & Pickens, 1980Hellmuth et al, 1991Hellmuth et al, , 1994, because of the induced dissolution/precipitation reactions (Jamtveit et al, 2009(Jamtveit et al, , 2011Putnis, 2002Putnis, , 2009White et al, 2001). These changes in pore geometry and connectivity during rock alteration are coupled with changes of mechanical properties (Ghaffari et al, 2013;Ghaffari & Young, 2011;Rock, 2010;Rossi & Graham, 2010).…”
Section: Introductionmentioning
confidence: 99%